Analysis on the Effect of Different Surgical Methods on the Treatment of Senile Osteoporotic Spinal Compression Fractures and the Influencing Factors of Complications. (1st September 2021) - Yu, Dejun; Liu, Zuyao; Wang, Hongqing; Yao, Ran; Li, Fu; Yang, Yang; Sun, Fenglong
Abstract : Osteoporotic fractures are a common type of fractures in the elderly, among which spinal compression fractures are more common. After the occurrence of fractures, due to the compression and burst of the vertebral body, this will lead to local kyphosis deformity and even affect the balance of the sagittal spine. In the past, conservative treatments were used for osteoporotic spinal compression fractures. Although it can relieve pain symptoms, it can easily lead to complications such as aggravation of osteoporosis and deep vein thrombosis of the lower extremities. At present, percutaneous vertebroplasty (PVP) and percutaneous kyphoplasty (PKP) are the main clinical surgical treatments, both of which are minimally invasive surgery, short operation time, effective pain relief, and rapid postoperative recovery. Although both of them are effective, there is still controversy over the efficacy of both in the treatment of osteoporotic spinal compression fractures. The purpose of this study was to investigate the efficacy of PVP and PKP in the treatment of elderly osteoporotic spinal compression fractures and to analyze the related factors that affect the occurrence of postoperative complications. The results show that both PVP and PKP can effectively improve the pain and dysfunction of elderly patients with osteoporotic spinal compression fracture, restoration of vertebral height, and correct kyphosis, but PKP has better effect and higher safety and is worth promoting. Postoperative complications of patients are related to their age, bone mineral density, use of hormones, and antiosteoporosis treatment.